Impact of COVID-19 Mandatory Social Isolation on the Development of Anxiety in Peruvian Dentistry Students: A Logistic Regression Analysis - Cayo-Rojas, César Félix,3 (2021)
The COVID-19 pandemic has generated much concern worldwide. Due to its high transmissibility, many young university students have had to carry out their academic activities in mandatory social isolation, which could generate excessive anxiety. Therefore, the aim of this study was to evaluate the anxiety levels in Peruvian dentistry students developed during COVID-19 mandatory social isolation. Materials and Methods: An analytical, observational, and transversal study was carried out in 403 dentistry students in the last two years from three Peruvian universities from May to July 2020. The Zung Self-Rating Anxiety Scale was used to detect anxiety symptoms and their respective diagnoses. A logit model was used to evaluate the association of the variables: age group (X1), gender (X2), type of university (X3), and marital status (X4), with the anxiety levels of the students, considering a p-value less than 0.05. Results: The prevalence of anxiety resulted in 56.8% (95% confidence interval (CI): 51.9–61.7) of 403 dentistry students. According to the multivariate logistic regression analysis, the type of university was the only variable that demonstrated to have a significant influence on the development of anxiety with an odds ratio (OR = 1.98; CI: 1.29–3.02); whereas the other variables such as age group (OR = 0.77; CI: 0.49–1.20), gender (OR = 1.15; CI: 0.72–1.84), and marital status (OR = 0.75; CI: 0.35–1.60) were not considered factors that influenced the development of anxiety. Conclusion: More than a half of the Peruvian dentistry students from three universities showed mild-to-severe anxiety levels. Students from a private university have a 98% higher chance of developing anxiety in comparison to students from public universities. Other variables such as gender, age group, or marital status were not considered influencing factors to develop anxiety.